THE EFFECT OF BRAINSTORMING TEACHING TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE PARAGRAPH - Ernawati - Gultom; Busmin - Gurning (Universitas Negeri Medan, 2014)
ABSTRACT This study aims to discover the effect of using Brainstorming Teaching Technique on students’ achievement in writing narrative paragraph. It was conducted by using experimental research design. The population of this research was the second grade students of SMA Swasta Raksana Medan. The samples of the research were two classes which consisted of experimental and control group which were chosen by using random sampling technique. Twenty one students were taken as the samples in each class. The experimental group was taught by using Brainstorming Teaching Technique, while the control group was taught by using lecturing technique. The instrument was used to collect the data by asking the students to write a narrative text. After analyzing the data, it was found that the value of t-observed was 5.51 with the degree of freedom (df) = 40 at the level of significance p(0.05)= 1.684. It means that t-observed was higher than t-table (5.51>1.684). The result of this study showed that teaching by using Brainstorming Teaching Technique was higher than that taught by using Lecturing Technique. Key Words : Brainstorming Teaching Technique, Writing Narrative * A graduate of English Language and Literature Department of UNIMED ** A lecturer of English Language and Literature Department of UNIMED